A simple calculation of the sea level trajectories over the Indian Ocean - RAO , G. V.; BOLHOFER , W. C.; BOOGAARD, H. M. E. VAN DE (MAUSAM, 1978)
Quasi-horizontal, 48-hr air trajectories are constructed over the Indian Ocean utilizing a mean sea level map for July and a series of daily maps in June 1970. The purpose of this calculation is to provide a field of trajectories based on the broad scale pressure gradient. Special emphasis is placed on those trajectories associated with the East African jet, the southern equatorial trough and the monsoon trough. Results included in this article showed that reasonably representative trajectories were calculated. Furthermore, the derived vorticity and divergence fields (not shown here) showed fair association with the significant synoptic features.